2011
DOI: 10.2174/1874318801105010019
|View full text |Cite
|
Sign up to set email alerts
|

Animal Health and Welfare Planning in Organic Dairy Cattle Farms

Abstract: Continuous development is needed within the farm to reach the goal of good animal health and welfare in organic livestock farming. The very different conditions between countries call for models that are relevant for different farming types and can be integrated into local practice and be relevant for each type of farming context. This article reviews frameworks, principles and practices for animal health and welfare planning which are relevant for organic livestock farming. This review is based on preliminary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…This will have severe structural and practical consequences for the way the farm is designed, organized, and managed, including the animals. European action research projects demonstrated how emphasizing farmer ownership in decision-making, empowerment, knowledge exchange, and common learning can mediate significant change on the farm level (Anonymous 2010;Vaarst 2007;Ivemeyer et al 2010;Vaarst et al 2010;Bennedsgaard et al 2010). On the sector level, the constant debate in combination with addressing and involving relevant actors such as decision makers, citizens, and politicians, can stimulate further development of livestock systems with high animal welfare in accordance with the basic organic principles, even in situations where the agricultural sector is under great pressure, e.g., economical pressure to produce more for less money.…”
Section: Tropical Organic Livestock Systemsmentioning
confidence: 99%
“…This will have severe structural and practical consequences for the way the farm is designed, organized, and managed, including the animals. European action research projects demonstrated how emphasizing farmer ownership in decision-making, empowerment, knowledge exchange, and common learning can mediate significant change on the farm level (Anonymous 2010;Vaarst 2007;Ivemeyer et al 2010;Vaarst et al 2010;Bennedsgaard et al 2010). On the sector level, the constant debate in combination with addressing and involving relevant actors such as decision makers, citizens, and politicians, can stimulate further development of livestock systems with high animal welfare in accordance with the basic organic principles, even in situations where the agricultural sector is under great pressure, e.g., economical pressure to produce more for less money.…”
Section: Tropical Organic Livestock Systemsmentioning
confidence: 99%
“…These studies emphasize the initial assessment and evaluation of health and welfare by an external person, implementation of farm-specific measures, and constant review and adaptation of measures as key aspects. The structured process includes farmer ownership of goals and measures, involvement of all relevant people, and the acknowledgment of good aspects on the farm (Vaarst et al, 2011;Tremetsberger and Winckler, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The perceptions of both the farmers and the veterinarians are crucial if the relationship is to be satisfying and fulfil the objectives of improved health and economical benefits for both parties [20]. According to [21] "Respectful communication between the owner of the herd and other farmers as well as animal health and welfare professionals (veterinarians and advisors) is paramount." The perception of veterinarians by dairy cow farmers, even in conventional farms, falls within one of two groups: : one group sees the veterinarian as a repairman that identifies pathologies and cures them, and the other group demands technical advice for previously identified problems.…”
Section: Discussionmentioning
confidence: 99%